Trends in the Rates of Pediatric Pyeloplasty for Ureteropelvic Junction Obstruction over 19 Years: A PHIS Database Study - Ardavan Akhavan; Paul A. Merguerian; Cindy Larison; Adam B. Goldin; Margarett Shnorhavorian (Advances in Urology)
Background. Over the past 20 years, the management of ureteropelvic junction obstruction (UPJ) has shifted. While many urologists note a decrease in the number of pyeloplasties performed over time, the nature of the change in practice has yet to be defined. In the current study, we utilize a national, multi-institutional database of children’s hospitals to evaluate trends in patients undergoing pyeloplasty as well as the rate of surgical reconstruction over the past 20 years. Material/Methods. We queried the Pediatric Health Information System (PHIS) database for all children undergoing primary pyeloplasty between 1992 and 2011. Clinical variables, including age at time of surgery, gender, length of stay (LOS), and geographic region, were determined. Age-adjusted rate of repair was also calculated per 100,000 PHIS inpatients. Results. 6,013 patients were included in the study, of which 71.6% were male and 64.2% were under the age of 24 months at time of surgery. Over the study period, the median age at time of surgery increased from 2–4 months to 12–14 months (P<0.01). LOS decreased from a median of 5 days to 2 days (P<0.001). The rate of surgery increased by 10.6 pyeloplasties per 100,000 PHIS inpatients from 1992 to 2011 (P<0.01). The highest rate of pyeloplasty was in the northeast. The increase in pyeloplasties performed from 1992 to 1999 was specific to children aged greater than 24 months, while rates stayed the same in infants younger than 2 years during the same time period. In contrast, from 1999 to 2011, the rate of pyeloplasty decreased in patients less than 2 years of age, while the rate remained constant in patients over age 2. Conclusion. The rate of pyeloplasty increased in PHIS hospitals from 1992 to 2011. Trends are due to an increase in surgery in infants younger than 2 years from 1992 to 1999, followed by a progressive surgical rate decline, characterized by a shift towards patients older than 2 years of age.